Research on the effect of managerial pro-social rule breaking on miner safety deviance behavior - Wenping LIU; Xiaoguang LIU (Meikuang Anquan)
In order to explore the influence mechanism of managerial pro-social rule breaking on miner safety deviance behavior, based on existing research, this study introduces the sense of self-control resource depletion threat, system awe, expected coworkers’ safety deviance and expected coworkers’ moral condemnation of safety deviance as mediating variables, and establishes a multiple mediation model of the influence of managerial pro-social rule breaking on miners safety deviance behavior. 391 miners from 3 coal mines were used as research objects to collect research data through three time-point follow-up questionnaires, and SPSS and Mplus were used for data analysis to verify the research hypothesis. The results show that the managerial pro-social rule breaking positively affects the miners’ safety deviance behavior, and the sense of self-control resource depletion threat, system awe, expected coworkers’ safety deviance and expected coworkers’ moral condemnation of safety deviance play some mediating roles.